Die Beurteilung von Lehrwerken für Deutsch als Fremdsprache anhand des Gemeinsamen Europäischen Referenzrahmens für Sprachen - Retelj, Andreja (Linguistica (Ljubljana), 2014)
The Common European Framework of Reference for Languages: Learning, Teaching, Assessment (CEFR) has since its inception in 2001 served as a guideline not only for teachers and students, but also for curriculum writers, test developers, and textbook authors. CEFR was only translated into Slovenian in 2011. The key principle of CEFR is an action-oriented approach that defines the communicative competence of an individual on the basis of the language activities of reception (listening, reading), production (spoken and written), interaction (spoken), and mediation. Each individual skill is defined by descriptors for levels A1-C2. The aim is to ensure more transparency in the process of language teaching and learning and at the same time to enable students to develop their foreign-language communication competence in an efficient way. Given that foreign language textbooks greatly influence the way a foreign language is taught, the article tries to determine how the students% lexical competence at different levels (as defined by CEFR) is developed with the aid of some of the most commonly used German language textbooks.
Keywords: allemand; besedišče; Cadre européen commun de référence pour les langues; CECRL; compétence lexicale; German; leksikalna zmožnost; manuels de langue; nemščina; SEJO; Skupni evropski jezikovni okvir; tuji jeziki; učbeniki; vocabulaire